2017
DOI: 10.2217/fvl-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 Enhances the Energy Metabolism of Human Umbilical Cord Mesenchymal Stem Cells to Promote Virus Infection

Abstract: Aim: To explore the underlying influence of HSV type-1 (HSV-1) infection on the energy metabolism of human umbilical cord-derived mesenchymal stem cells (UCMSCs). Methods: UCMSCs (derived from different donors) were isolated from umbilical cord tissue, cultured and infected with HSV-1. Various virology and biochemical assays were used to assess cell viability and function, such as plaque formation assay and mitochondrial mass assay. Results: HSV-1 infection sharply activated mitochondrial biogenesis, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The HSV-1 protein UL-16 also targets mitochondria and increases oxidative phosphorylation and ATP generation [34]. Moreover, inhibition of terminal oxidation was shown to inhibit HSV-1 replication in human umbilical cord-derived mesenchymal stem cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…The HSV-1 protein UL-16 also targets mitochondria and increases oxidative phosphorylation and ATP generation [34]. Moreover, inhibition of terminal oxidation was shown to inhibit HSV-1 replication in human umbilical cord-derived mesenchymal stem cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that HSV increases OXPHOS, glucose consumption, and lactate production. These enhancements occur through elevating glucose uptake, and upregulation of PFKM (PFK‐1) activity, as well as PGC‐1α, NDUFB‐3, and CYC‐1 genes 111,112 . The activation of the glycolysis pathway can produce more pyruvate into mitochondria and increase OXPHOS, generating ATP 113 .…”
Section: Herpersviridaementioning
confidence: 99%
“…These enhancements occur through elevating glucose uptake, and upregulation of PFKM (PFK-1) activity, as well as PGC-1α, NDUFB-3, and CYC-1 genes. 111,112 The activation of the glycolysis pathway can produce more pyruvate into mitochondria and increase OXPHOS, generating ATP. 113 HSV-1 infection leads to elevated levels of PEP.…”
Section: Herpes Simplex Virus 1 (Hsv-1)mentioning
confidence: 99%